A new technique to classify the compatibility of wood with cement (Wood science and technology, 1990)
Wood-cement panels have commanded renewed interest during the last decade be- cause of their potential application in the building industry. Several methods to classify wood of various species regarding its compatibility with cement have been established in the literature based on hydration measurements in Dewar flasks. These ranking methods lack consistency in the classification of species because the hydration conditions vary among laboratories. Three techniques for evaluating wood-cement compatibility were established and compared. The best technique is based on a wood-cement compatibility factor which is the ratio of the area under the wood-cement hydration heat rate curve to that of neat cement. The area is calculated on 24-h basis starting from the initial cement set time. This area ratio method ranks species over a 100% scale and accounts well for species that are totally incompatible.